Systematic Literature Review (SLR) of Urban Temporality Flexible and Adaptive Spatial Design Strategies in Urban Context - Khansa Aulia Ekaputri; Arnis Rochma Harani; Asrul M. R Aminuddin (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2025)
Urban temporality has become an emerging field of study in architecture and urban design, offering new perspectives on understanding urban space. However, systematic reviews of the evolution of this discourse remain limited. This study applies a Systematic Literature Review (SLR) using the PRISMA methodology to analyze the development of the concept of urban temporality in academic literature over the past decade. 200 publications containing "urban" and "temporality" were screened and assessed for eligibility, resulting in 25 studies analyzed bibliometrically. The findings identify six main themes, including Space Experience by Body Sense, Mobilities, Space Development, Spatial Dynamics, Infrastructure and Social Development, and Smart City. Trend analysis reveals a shift in focus from "rhythm" (2014–2019) to "social behavior" (2019–2024), reflecting a change in research orientation. This study contributes to mapping the thematic development and provides a foundation for future research into urban temporality.